On fractional Caputo operator for the generalized glucose supply model via incomplete Aleph function - Himani Agarwal; Manvendra Narayan Mishra; Ravi Shanker Dubey (International Journal of Mathematics for Industry)
In this paper, we have attempted a fresh method to demonstrate how special functions and fractional calculus are used in real-world problems. Here, we have examined the glucose supply in human blood using the incomplete Aleph function (IAF) and the Caputo fractional operator. In this study, we used the incomplete Aleph function to find the blood glucose equation that is supplied to human blood. In terms of various hyper-geometric functions, we have also obtained several significant and unique results, and we have defined the blood glucose function in terms of IAF.